A escrita trans como potência: subjetividades e epistemologias no livro “Eu Travesti” de Luísa Marilac (2019) - Silva, Andrey Tironi da (2024)
This study explores the analysis of travesti autobiographies, specifically the book "Eu, Travesti – Memórias de Luísa Marilac" (2021), written by Luísa Marilac in collaboration with journalist Nana Queiroz. The book was chosen with the intention and possibility of analyzing how the autobiographical resource written by trans women and travestis constitutes a means of developing epistemologies in the field of gender studies. Furthermore, the theme of trans autobiography allows us to work with broader concepts beyond what is usually proposed for this type of source, such as the concept of trans escrevivência and transfeminism. This research seeks to understand and analyze how the lives of transgender and travesti people can be seen and understood as knowledge producers within our cisgender society, considering that writing is a form of subjectivation for all individuals.